2023
DOI: 10.1002/hsr2.1405
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of general anxiety disorder among nursing students and its associated factors

Abstract: Background: University training in nursing together with other student variables can increase the risk of anxiety in students. It is important to assess the student's level of anxiety, which can have repercussions on their training and mental health. There are several validated tools such as the generalized anxiety disorder scale (GAD-7).Objective: To know which factors are associated with the appearance of anxiety and which protect against it in university nursing students.Method: A cross-sectional descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Several factors that predict academic stress and achievement are associated with life satisfaction, psychological well-being, one’s relationship with happiness, and one’s locus of control [ 10 ]. One study found that 66.5% of surveyed nursing students had experienced varying levels of anxiety crises, with 48.8% of these students choosing not to seek assistance for mitigation of their anxiety or stress [ 11 ]. Academic stress has been linked to health concerns such as physical exhaustion, sleeping disorders, irritability, negative thoughts, and heightened nervousness [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors that predict academic stress and achievement are associated with life satisfaction, psychological well-being, one’s relationship with happiness, and one’s locus of control [ 10 ]. One study found that 66.5% of surveyed nursing students had experienced varying levels of anxiety crises, with 48.8% of these students choosing not to seek assistance for mitigation of their anxiety or stress [ 11 ]. Academic stress has been linked to health concerns such as physical exhaustion, sleeping disorders, irritability, negative thoughts, and heightened nervousness [ 12 ].…”
Section: Introductionmentioning
confidence: 99%